Efficacy and safety of male fertility-sparing radical cystectomy with orthotopic neobladder versus radical cystectomy and nerve-sparing cystectomy: a meta-analysis - Huang, Yu; Shi, Hongjin; Wang, Qun; Wang, Zhengyan; Wang, Rui; Zhang, Yawei; Wang, Jiansong; Zhang, Nan; Fu, Shi; Wang, Haifeng (Frontiers in Oncology, 2025)
BackgroundRadical cystectomy (RC) serves as the gold standard treatment for organ-localized bladder cancer; however, postoperative complications diminish the quality of life of patients. Whether male fertility-sparing radical cystectomy(FSRC) with orthotopic neobladder (ONB) surpasses RC and nerve-sparing cystectomy (NSC) remains controversial. The objective of this study is to compare the efficacy and safety of the two surgical approaches.MethodsIn accordance with the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) statement, PubMed, Web of Science, Embase, CNKI databases, Medline, and Cochrane Library were searched until June 2024. Eligible studies were identified in line with the inclusion and exclusion criteria.ResultsA total of 10 studies encompassing 1104 patients were incorporated in this study. The outcomes demonstrated that fertility-sparing radical cystectomy (FSRC) presented significant superiority in erectile function (EF) (OR: 12.67; 95% CI 3.27-49.03; P<0.001), daytime urinary continence (OR: 5.91; 95% CI, 1.83-19.13; P = 0.003), and nocturnal urinary continence (OR: 5.13; 95% CI, 1.98-13.34; P<0.001) over non-fertility-sparing radical cystectomy (nFSRC). Compared with nFSRC, the incidences of postoperative prostate cancer (RD:−0.10; 95% CI, -0.21-0.10; P = 0.086), tumor local recurrence (OR:0.51; 95% CI, 0.26-1.00; P = 0.052), tumor metastasis (RD:-0.02; 95% CI, -0.09-0.06; P = 0.665) and 2-year survival (OR:1.21; 95% CI, 0.63-2.30; P = 0.567) after surgery were comparable. In the subgroup analysis, some differences in outcome measures were identified based on sample size, study type, control group, and study area.ConclusionUnder rigorous preoperative screening, male FSRC with ONB demonstrates certain efficacy and safety in the treatment of bladder cancer, particularly among younger patients, warranting broader clinical consideration. More relevant clinical RCTs are required.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024558576